Regional Diversity of Employment Structure by Level of Education and Occupational Groups in Poland - Gajdos, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The main purpose of this paper is to present changes in working force structure in cross-section of level of education and major occupational groups in Poland on voivodeship (regional) level. Spatial differentiation of human capital quality is the main element of education policy. Also, the assessment of the transformation process to economy based on knowledge requires cross-section data analysis, spatial as well. Data which concern labour force structure in level of education and major occupational groups in voivodeship cross-section taken from Labour Force Survey have been used in this paper. The data source specificity enables the assessment of labour force professional specialization on voivodship level and the changes of this specialization with time. Combined analysis of spatial and structural changes with the method of time-series-cross-section data analysis makes it possible to draw conclusions about processes occurring on regional labour markets. It is especially important in the context of education policy implementation.